2013
DOI: 10.1155/2013/801284
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Topology Reformation Algorithm for Power Saving in ZigBee Sensor Networks

Abstract: ZigBee is a protocol suite based upon IEEE standard 802.15.4 for the construction of low-rate wireless personal area networks. Since most of ZigBee devices are powered by battery, the power saving is an important issue. In the past several years, many solutions are proposed to extend battery life by reducing device transmitting and receiving time. However, few studies have noticed that most energy is consumed in sensing and monitoring rather than communicating activities, since the data rates in most ZigBee ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The radio of the CC2530 chip can easily be built on top of the IEEE 802.15.4 based standard protocols such as RemoTI, TIMAC, and Z-Stack. However, take the power consumption of these protocols into consideration, we finally choose the Z-Stack protocol as our application platform [11]. For the design of the antenna, a small 2.4 GHz antenna was made in the printed circuit board which largely reduced the size of the node compared with the whip antenna.…”
Section: Wireless Communication Modulementioning
confidence: 99%
“…The radio of the CC2530 chip can easily be built on top of the IEEE 802.15.4 based standard protocols such as RemoTI, TIMAC, and Z-Stack. However, take the power consumption of these protocols into consideration, we finally choose the Z-Stack protocol as our application platform [11]. For the design of the antenna, a small 2.4 GHz antenna was made in the printed circuit board which largely reduced the size of the node compared with the whip antenna.…”
Section: Wireless Communication Modulementioning
confidence: 99%
“…Many work in this area of energy saving have shown that energy is consumed in sensing and monitoring the surrounding area as compared to the data packet exchange activities [1]. Excluding, energy consumption in the nodes such as forwarding nodes and gateway nodes in cluster are higher than other sensing nodes in the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…The most important issue considered when planning WSN Cluster is the energy consumption per node and how the next protocol can improve this. By switching node activities the power consumed is optimized leads to the increased network life time [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations